2015
DOI: 10.1007/s12275-015-4672-9
|View full text |Cite
|
Sign up to set email alerts
|

Genipin as a novel chemical activator of EBV lytic cycle

Abstract: Epstein-Barr virus (EBV) is a ubiquitous gammaherpesvirus that causes acute infection and establishes life-long latency. EBV causes several human cancers, including Burkitt's lymphoma, nasopharyngeal and gastric carcinoma. Antiviral agents can be categorized as virucides, antiviral chemotherapeutic agents, and immunomodulators. Most antiviral agents affect actively replicating viruses, but not their latent forms. Novel antiviral agents must be active on both the replicating and the latent forms of the virus. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 27 publications
1
32
0
1
Order By: Relevance
“…Unlike genipin, geniposide did not show any bactericidal activity or toxicity to AGS cells at concentrations less than 10 mM. Genipin has been shown to have antiinflammatory, anti‐angiogenic, anti‐proliferative, and hepatoprotective activities in several cell lines, including murine macrophage cells, human umbilical vein endothelial cells, human breast cancer cells, human colon and prostate cancer cells, and human hepatocarcinomic leukemia cells (Suzuki and others ; Shoda and others ; Koo and others ; Kojima and others ; Jeon and others ; Son and others ; Ko and others ). Ko and others demonstrated that the induction of apoptosis and G 2 /M phase arrest by genipin (50 to 100 μM) inhibits cell proliferation in AGS cells through the Egr1/p21 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike genipin, geniposide did not show any bactericidal activity or toxicity to AGS cells at concentrations less than 10 mM. Genipin has been shown to have antiinflammatory, anti‐angiogenic, anti‐proliferative, and hepatoprotective activities in several cell lines, including murine macrophage cells, human umbilical vein endothelial cells, human breast cancer cells, human colon and prostate cancer cells, and human hepatocarcinomic leukemia cells (Suzuki and others ; Shoda and others ; Koo and others ; Kojima and others ; Jeon and others ; Son and others ; Ko and others ). Ko and others demonstrated that the induction of apoptosis and G 2 /M phase arrest by genipin (50 to 100 μM) inhibits cell proliferation in AGS cells through the Egr1/p21 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that genipin has an antiinflammatory ability (Jeon and others ), a bile secretion‐enhancing effect (Shoda and others ), and an anti‐thrombotic effect (Suzuki and others ). Genipin has been found to inhibit the Epstein–Barr virus (EBV) and EBV‐associated stomach carcinoma proliferation (Son and others ). In addition, genipin has been observed to induce AGS human stomach cell apoptosis via the p53‐independent Egr1/p21 signaling pathway (Ko and others ).…”
Section: Introductionmentioning
confidence: 99%
“…68 Genipin exhibited anti-tumor and anti-viral effects against Epstein-Barr virus (EBV) and EBV associated gastric carcinoma (EBVaGC) by significant cytotoxicity via inducing methylation on EBV C promoter and tumor suppressor gene BCL7A, arresting cellcycle progress (S phases), up regulating EBV latent/lytic genes, stimulating EBV progeny production, activating EBV F promoter for EBV lytic activation in SNU719 cells and suppressed EBV infection. 107 Iridoid glycosides (IGs) exhibited anti-viral activity against influenza A virus via inhibition of intracellular acidification and Ca 2+ influx during fusion and uncoating of influenza replication cycle. 41 Protective and anti--apoptotic activities of GJE glycoprotein in 100μg/ml exhibited significantly on the glucose/glucose oxidase (G/GO)-induced or hypoxanthine/xanthine oxidase (HX/XO)-induced cytotoxicity and apoptosis systems in NIH/3T3 cells, DNA fragmentation respectively by blocking activities against cytotoxicity and apoptosis; the activation of redox-sensitive signal mediators, protein kinase C alpha (PKCα) and nuclear factor-kappa B (NF-κB) in G/GO or HX/XO-induced apoptotic NIH/3T3 cells.…”
Section: Anti-apoptotic and Anti-cancer Activitiesmentioning
confidence: 99%
“…Genipin 1 , an iridoid derived from the glycoside geniposide 2 (Figure ), is present in the fruit of the Gardenia jasminoides Ellis . It is isolated on a commercial basis from the fruit extracts by treatment with β‐glucosidase.…”
Section: Introductionmentioning
confidence: 99%
“…Genipin 1, an iridoid derived from the glycoside geniposide 2 (Figure 1), 1,2 is present in the fruit of the Gardenia jasminoides Ellis. 3 It is isolated on a commercial basis from the fruit extracts by treatment with β-glucosidase. This Gardenia fruit has long been used in traditional Chinese medicine and has been reported to possess a number of pharmacological properties including neuroprotective activity 4 and is also the source of Gardenia Blue, which is widely used in Eastern Asia as a natural food colourant.…”
Section: Introductionmentioning
confidence: 99%